2022
DOI: 10.3389/fphar.2022.948939
|View full text |Cite
|
Sign up to set email alerts
|

Multi metabolomics-based analysis of application of Astragalus membranaceus in the treatment of hyperuricemia

Abstract: Hyperuricemia (HUA) is a common metabolic disease that is an independent risk factor for comorbidities such as hypertension, chronic kidney disease, and coronary artery disease. The prevalence of HUA has increased over the last several decades with improved living standards and increased lifespans. Metabolites are considered the most direct reflection of individual physiological and pathological conditions, and represent attractive candidates to provide deep insights into disease phenotypes. Metabolomics, a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Compared with the MC group, it was found that 196 serum metabolites were significantly upregulated and 362 metabolites were significantly downregulated in the TAP group in positive mode. Meanwhile, it was found that 210 serum metabolites were significantly upregulated and 355 metabolites were significantly downregulated in positive mode, suggesting that TAP altered the metabolite profiles of PO-induced HUA, similar to the effect of Astragalus membranaceus …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Compared with the MC group, it was found that 196 serum metabolites were significantly upregulated and 362 metabolites were significantly downregulated in the TAP group in positive mode. Meanwhile, it was found that 210 serum metabolites were significantly upregulated and 355 metabolites were significantly downregulated in positive mode, suggesting that TAP altered the metabolite profiles of PO-induced HUA, similar to the effect of Astragalus membranaceus …”
Section: Resultsmentioning
confidence: 92%
“…Meanwhile, it was found that 210 serum metabolites were significantly upregulated and 355 metabolites were significantly downregulated in positive mode, suggesting that TAP altered the metabolite profiles of POinduced HUA, similar to the effect of Astragalus membranaceus. 49 Variable importance for the projection (VIP) is used to measure the expression patterns of various metabolites and explore biologically significant differential metabolites. The screening criteria for significantly different metabolites in this paper are VIP >1 and a P value < 0.05.…”
Section: Effects Of Tap On Serum Andmentioning
confidence: 99%
“…Principal component analysis (PCA) is a representative of unsupervised algorithms, which can reflect the spatial distribution of the original data of the samples without any artificial factor grouping. The closer the spatial distribution of the samples to each other, the closer the composition of the metabolite components within the samples [ 22 , 23 , 24 ]. In the current research, PCA was carried out to discern the differences of metabolite fingerprints in serum among NG, MG, and DG.…”
Section: Resultsmentioning
confidence: 99%
“…More excitingly, many studies have reported that RA can treat hyperuricemia. 15 , 16 However, RA is composed mainly of flavonoids, saponins and polysaccharides, which are difficult to absorb directly in the digestive tract. 17 , 18 Therefore, it is important to understand the mechanism of RA in improving hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%